Wear of materials used in dentistry: a review of the literature - Sulong, Mohd Zainal Abidin Mohd; Aziz, Ramlah Abdul (Elsevier, 1990)
This is a review of the literature concerning wear related to the following materials used in dentistry: dental amalgam, composite resins, and glass-ionomer cements, as well as natural tooth substance. Discussions are included on both in vivo and in vitro studies in which various methods were used to help determine wear resistance.